1997
DOI: 10.1002/(sici)1097-4679(199712)53:8<809::aid-jclp4>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of PTSD symptoms in a community exposed to serial murder

Abstract: This study examined the presence of PTSD symptoms across time in a community exposed to serial murder. One hundred eighty four subjects (48% response rate) responded to the initial survey while 64 and 30 subjects, respectively, participated in the 9- and 18-month follow-up studies. Results indicated widespread endorsement of PTSD symptoms following the murders. The most severe reactions were found among residents demographically similar to the victims. PTSD symptoms, while not transient, appeared to decrease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Moreover, there was considerable attrition across time. However, the level of attrition was comparable to other longitudinal studies examining PTSD symptoms (e.g., Herkov & Biernat, 1997), and the response rates at each time point were comparable to other survey studies throughout social science literatures (for a review, see Feil et al, 2007). There is, however, no theoretical reason to believe that these limitations would influence the relationships found within the current sample.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, there was considerable attrition across time. However, the level of attrition was comparable to other longitudinal studies examining PTSD symptoms (e.g., Herkov & Biernat, 1997), and the response rates at each time point were comparable to other survey studies throughout social science literatures (for a review, see Feil et al, 2007). There is, however, no theoretical reason to believe that these limitations would influence the relationships found within the current sample.…”
Section: Discussionsupporting
confidence: 76%
“…Although some researchers have identified the hyperarousal cluster as particularly important in predicting the development of PTSD (O'Donnell, Elliott, Lau, & Creamer, 2007; Schell, Marshall, & Jaycox, 2004; Solomon, Horesh, & Ein-Dor, 2009), others have found reexperiencing symptoms to be more frequently endorsed (Rasmussen, Smith, & Keller, 2007) and to be associated with more severe PTSD (Conrad et al, 2004). Additional research has suggested that avoidance symptoms are endorsed most frequently (Kopel & Friedman, 1997) and are more likely to persist over time (Herkov & Biernat, 1997; Marshall et al, 2006; Perkonigg et al, 2005; Solomon et al, 2009), with some researchers noting that the numbing symptoms of that cluster are often most strongly associated with current PTSD (Foa et al, 1995; Marshall et al, 2006). At the same time, however, others have found avoidance symptoms to be associated with lower severity of PTSD (Betemps et al, 2003).…”
mentioning
confidence: 99%
“…Because of the difficulties associated with the refugee experience, researchers have linked the amount of trauma refugees experience with poor emotional outcomes (Almqvist & Brandell-Forsberg 1997;Herkov & Biernat 1997;Mollica et al 1998). It is not surprising, therefore, that research indicates "higher rates of symptoms and mental disorders in refugees, compared with the general population" (Williams & Berry 1991 p. 632).…”
Section: Literature Reviewmentioning
confidence: 99%